2021
DOI: 10.1039/d0sc06451c
|View full text |Cite
|
Sign up to set email alerts
|

Defective TiO2for photocatalytic CO2conversion to fuels and chemicals

Abstract: This review discusses photocatalytic CO2 conversion using defective TiO2, with emphasis on the mechanism, the role of defects on CO2 adsorption–activation and product selectivity, as well as challenges of defective TiO2 to produce solar fuels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 90 publications
0
51
0
3
Order By: Relevance
“…shows the SPS of obtained samples to investigate the separation and transfer of photogenerated charge carriers in them under the simulated solar illumination. The Sn x Nb 1−x O 2 solid solution sample had a significantly higher surface photovoltage than that of the pristine SnO 2 sample, which indicated that the formation of Sn x Nb 1−x O 2 solid solution by the heavy Nb-doping could significantly promote the separation and transfer of photogenerated charge carriers due to the formation of oxygen vacancies, and subsequently enhance its photocatalytic performance [25][26][27][28]. Figure 5(b) compares their Nyquist plots obtained from the EIS measurements in darkness and under the simulated solar illumination.…”
Section: Separation and Transfer Of Photogenerated Charge Carriers Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…shows the SPS of obtained samples to investigate the separation and transfer of photogenerated charge carriers in them under the simulated solar illumination. The Sn x Nb 1−x O 2 solid solution sample had a significantly higher surface photovoltage than that of the pristine SnO 2 sample, which indicated that the formation of Sn x Nb 1−x O 2 solid solution by the heavy Nb-doping could significantly promote the separation and transfer of photogenerated charge carriers due to the formation of oxygen vacancies, and subsequently enhance its photocatalytic performance [25][26][27][28]. Figure 5(b) compares their Nyquist plots obtained from the EIS measurements in darkness and under the simulated solar illumination.…”
Section: Separation and Transfer Of Photogenerated Charge Carriers Of...mentioning
confidence: 99%
“…Various approaches had been proposed and proved to be effective to enhance the photocatalytic CO 2 reduction efficiency, including impurity doping [19,20], metal deposition [21], heterojunction construction [22], cocatalyst loading [23], and modulating acid-base properties [20,24]. Among them, the creation of defects, such as vacancies or substitutions, could markedly influence the distribution of photogenerated charges to enhance the CO 2 activation [25][26][27], and serve as surface reactive sites for the reduction reaction [28], which is promising in the design and creation of novel photocatalysts for highly efficient CO 2 reduction.…”
Section: Introduction mentioning
confidence: 99%
“…Titania (TiO 2 ) is a well-known semiconductor photocatalyst. Considering its excellent chemical stability, hydrophilicity, eco-friendliness, nontoxicity, and low cost, this material has been extensively studied in recent years. , The unique band-gap energy (3.2 eV of anatase) of TiO 2 facilitates the generation of electron–hole pairs by ultraviolet light irradiation, resulting in effective redox performance and organic pollutant degradation. , The P25-type TiO 2 is particularly popular due to its good photocatalytic activity and accessibility. However, TiO 2 nanoparticles are incredibly prone to agglomerate so that it is hard to be recycled as a catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we sought to construct a multifunctional nanostructure to manipulate O 2 activation using TiO 2 as the primary building block. 23 The first ingredient we considered was the oxygen vacancies (OVs), which are the most common anion defects to promote oxygen adsorption and diffusion. 24,25 The second building block we thought of was Ru due to the following two reasons.…”
Section: Introductionmentioning
confidence: 99%